Experimental study on full-penetration friction stir welding of 2219 aluminum alloy - Sun Qian; Zhou Hong; Wu Zaihou (Functional Materials, 2018)
This paper takes 2219 aluminum alloy as the object of study, makes an experiment of full-penetration friction stir welding (FSW). The effectiveness of three kinds of full penetration procedure are verified by using technology of X-ray flaw test and root color test, and the differences of mechanical property of weld bead of three FSW have been analyzed based on mechanical property and metallographic tests. Through the experiment, the FSW of back supporting can be proved to be the most suitable welding procedure for production.